Carbon fibre buckle arrestors for offshore pipelines. (June 2021) - Alrsai, Mahmoud; Karampour, Hassan; Hall, Wayne; Lindon, Alex K.; Albermani, Faris
Abstract: Feasibility and efficiency of using carbon fibre reinforced polymer (CFRP) buckle arrestors in steel offshore pipelines with D/t of 28 and 40 are investigated using hyperbaric chamber tests. CFRP arrestors are manufactured using Prepreg (PP), Wet-Layup (WL) and Vacuum Bagging (VB) curing methods, with coarse and fine sand surface preparations. A parametric study is performed that outlines the performance of CFRP arrestors in various geometric configurations. Efficiency of CFRP arrestors using different manufacturing methods and various geometric configurations are calculated and compared with those of conventional steel buckle arrestors. It is shown that the efficiencies of CFRP arrestors vary between 0.74 and 1.0 for different manufacturing methods. Optimum efficiencies are obtained in the WL technique, using fine sanding, with CFRP arrestor of thickness twice the steel pipe-wall thickness, and fibres oriented in the hoop direction. Results show that at similar efficiencies, the CFRP arrestors can be much thinner than conventional slip-on or integral arrestors.